Pengaruh Kompetensi dan Skeptisme Profesional terhadap Kemampuan Pendeteksian Kecurangan dengan Time Budget Pressure sebagai Variabel Moderasi - Sharon, Patricia Rebeca; Yanti, Harti Budi (Universitas Batanghari Jambi, 2025)
his study aims to determine the effect of auditor competence and professional skepticism with time budget pressure as a moderating variable on the ability to detect fraud. The population in this study is external audits at Public Accounting Firms in Jakarta. This type of research is quantitative. The sampling technique used is purposive sampling. The analytical tools used include validity and reliability tests and hypothesis testing. The results show that auditor competence and professional skepticism have a positive effect on the ability to detect fraud. In addition, this study also found that time budget pressure does not moderate the influence of auditor competence and professional skepticism on the ability to detect fraud at Public Accounting Firms in Jakarta.